Develop Your Public Speaking Skills: Tips for Beginning Speakers, Speech Coaches, and Judges - Marshall H. Breeze; Rick D. Rudd; Gregory T. Gifford; Catherine W. Shoulders (EDIS)
Developing effective public speaking skills is one of the most valuable benefits young people can derive from participation in 4-H, FFA, and other youth groups. This revised 7-page fact sheet pulls together advice from textbooks and references on public speaking as well as actual critiques from judges of public speaking competitions to provide guidance that is both consistent with accepted practice for public speakers and relevant to the problems faced by young speakers in a competitive setting. It was written by Marshall H. Breeze, Rick D. Rudd, Gregory T. Gifford, and Catherine W. Shoulders and published by the UF Department of Agricultural Education and Communication, January 2011.